2004
DOI: 10.1063/1.1764938
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity measurements of two-dimensional self-assembled hexadecanethiol monolayers on polycrystalline gold

Abstract: The melting characteristics of hexadecanethiol two-dimensional self-assembled monolayers (SAMs) grown on polycrystalline Au surfaces are obtained via heat capacity measurements using nanocalorimetry at scanning rates of ∼30 000°C∕s. The analyzed amount of alkanethiol in the form of SAMs is typically in the 10−11 mol range. Melting occurs over a broad (full width on the half height ∼100°C) temperature range with a melting temperature of about 70°C, if the alkanethiol is partially desorbed from the Au surface du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…The specific heat capacity of the gold SAM surface has increased with temperature in the temperature region 100-300 K, and dropped down at 400 K. This change in the variation of the specific heat capacity of alkane thiol SAM on the gold surface with temperature is in reasonable agreement with the experimental results [42]. Zhang et al [42] have reported the melting transition temperature of the alkane thiol SAM on the gold surface from the observed change in the specific heat capacity value measured using calorimetry. The increase in the specific heat capacity in the temperature region 100-300 K may be attributed to the ordered, tilted conformation of the SAM chains.…”
Section: Structure and Specific Heat Capacitysupporting
confidence: 84%
“…The specific heat capacity of the gold SAM surface has increased with temperature in the temperature region 100-300 K, and dropped down at 400 K. This change in the variation of the specific heat capacity of alkane thiol SAM on the gold surface with temperature is in reasonable agreement with the experimental results [42]. Zhang et al [42] have reported the melting transition temperature of the alkane thiol SAM on the gold surface from the observed change in the specific heat capacity value measured using calorimetry. The increase in the specific heat capacity in the temperature region 100-300 K may be attributed to the ordered, tilted conformation of the SAM chains.…”
Section: Structure and Specific Heat Capacitysupporting
confidence: 84%
“…The SAM can separate the analyte of interest from interfering analytes and bring it closer to the nanostructured surface, analogous to the use of a stationary phase in high-performance liquid chromatography. Although SAMs have been useful for many applications, thermal desorption (70,71) and photooxidation (72)(73)(74) can result in defects in the coatings and thermodynamically unstable substrates (75).…”
Section: Surface-enhanced Raman Spectroscopy Sensingmentioning
confidence: 99%
“…In addition to the reduction in size of the equipment itself, MEMS techniques allow fabrication of nanocalorimeters with extremely low addenda enabling the use of minute amounts of sample ( van Herwaarden, 2005;Lerchner, Maskow, & Wolf, 2008;Queen and Hellman, 2009). Representative applications of these devices include investigation of thermal transitions of nanomaterials, thin-film materials, biological systems, and polymers as well as combustible gas sensing (Baier et al, 2005;Cavicchi et al, 2004;De Santis, Adamovsky, Titomanlio, & Schick, 2006Fominaya, Fournier, Gandit, & Chaussy, 1997;Guidi et al, 2002; van Herwaarden, Sarro, Gardner, & Bataillard, 1994;Johannessen, Weaver, Cobbold, & Coope, 2002;Lopeandia, 2005;Olson et al, 2000;Seung-Il, Mi-Hwa, Se-Chul, Jeon-Soo, & Yong-Jun, 2007Weiss, Igel, & Urban, 2007;Zhang et al, 2000Zhang et al, , 2004. Moreover, these devices have the potential of extending their use to other research fields where high sensitivity is required.…”
Section: Introductionmentioning
confidence: 97%